DISTRIBUTION AND MORTALITY PATTERNS IN PATIENTS CO-INFECTED WITH HIV AND TB IN KARELIA - Yu. M. Markelov; E. V. Pahomova; I. I. Rozhkova; Юрий Михайлович Маркелов; Екатерина Владимировна Пахомова; Инна Игоревна Рожкова (HIV Infection and Immunosuppressive Disorders, 2016)
The time course and distribution patterns of combined HIV/TB infection in the Republic of Karelia over the last eight years were studied. Additionally, 127 case histories of HIV/TB patients related to the period from 2001 to 2015 were examined. It is found that the high prevalence of multiple drug resistance of M. tuberculosis (primary MDR prevalence is 46,5%) is associated with delayed diagnoses of combined HIV/TB infection (stage 4-5 HIV in 70% of cases). This factor in combination with the significant input of HIV/TB patients from the Federal Penitentiary System promotes the rapid spread of HIV/TB infection over the whole territory of the Republic. These features make it expedient to develop dedicated programs aimed at close monitoring of risk groups and at the social support for homeless people and for convicts set free after imprisoning. With account of the high rate of other concomitant infections, the atypical clinical and roentgenologic manifestations of TB upon immunosuppression, and the high rate of MDR, speeding up of TB diagnosis requires the use of molecular diagnostic tools, such as Gene-X-Pert, when TB is suspected in HIV patients. Изучена динамика и особенности распространения сочетанной инфекции ВИЧ и туберкулеза за последние 8 лет на территории Республики Карелия. Дополнительно проведен анализ 127 историй болезни больных с сочетанной инфекцией ВИЧ+ТБ за период 2001-2015 годов. Выявлено, что на фоне широкого распространения множественной лекарственной устойчивости микобактерий туберкулеза в регионе (первичная МЛУ МБТ - 46,5%) имеет место поздняя диагностика сочетанной инфекции ВИЧ и туберкулеза (у 70% на 4-5 стадиях ВИЧ). Этот фактор наряду со значительным ежегодным притоком в гражданский сектор пациентов с сочетанной инфекцией из системы Управления федеральной службы исполнения наказания способствует дальнейшему быстрому распространению сочетанной инфекции на территории всей республики. Выявленные особенности социального состава и особенности распространения сочетанной инфекции требуют ...